Characterization of kinesiological patterns of the frontal kick, mae-geri, in karate experts and non-karate practitioners (Revista de Artes Marciales Asiáticas, 2014)
Presently, coaches and researchers need to have a better comprehension of the kinesiological parameters that should be an important tool to support teaching methodologies and to improve skills performance in sports. The aim of this study was to (i) identify the kinematic and neuromuscular control patterns of the front kick (mae-geri) to a fixed target performed by 14 experienced karate practitioners, and (ii) compare it with the execution of 16 participants without any karate experience, allowing the use of those references in the analysis of the training and learning process. Results showed that the kinematic and neuromuscular activity during the kick performance occurs within 600 ms. Muscle activity and kinematic analysis demonstrated a sequence of activation bracing a proximal-to-distal direction, with the muscles presenting two distinct periods of activity (1, 2), where the karateka group has a greater intensity of activation – root mean square (RMS) and electromyography (EMG) peak – in the first period on Rectus Femoris (RF1) and  Vastus Lateralis (VL1) and a lower duration of co-contraction in both periods on Rectus Femoris-Biceps Femoris and Vastus Lateralis-Biceps Femoris (RF-BF; VL-BF). In the skill performance, the hip flexion, the knee extension and the ankle plantar flexion movements were executed with smaller difference in the range of action (ROA) in the karateka group, reflecting different positions of the segments. In conclusion, it was observed a general kinesiological pattern, which was similar in karateka and non-karateka practitioners. However, in the karateka group, the training induces a specialization in the muscle activity reflected in EMG and kinematic data, which leads to a better ballistic performance in the execution of the mae-geri kick, associated with a maximum speed of the distal segments, reached closer to the impact moment, possibly representing more power in the contact.